1986
DOI: 10.1002/ajh.2830210408
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained periparturient thrombocytopenia

Abstract: Since the advent of routine automated platelet counting we have observed unexplained periparturient thrombocytopenia (PPT) in an unexpected number of periparturient women, ie, during labor or within 24 hr postpartum. Mean +/- SD platelet count in 686 random blood donors was 236 +/- 50 X 10(9)/L and 1.02% had a platelet count less than 136 X 10(9)/L; in 2,204 random prenatal and postpartum women mean count was significantly higher (275 +/- 86 X 10(9)/L; p less than 0.001). Of 1,621 periparturient women, 74 (4.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…10 9 /l and ^135 ! 10 9 /l, respectively) in the peripartum phase [4,5], giving rise to a new clinical entity, 'gestational thrombocytopenia' [6]. In a recent longitu-dinal cohort study, we found that similar percentages of women exhibited similar and significant increases or decreases in the platelet count during the third trimester, which would explain why the mean platelet count reportedly shows no apparent change during normal pregnancy [7].…”
Section: Introductionmentioning
confidence: 76%
“…10 9 /l and ^135 ! 10 9 /l, respectively) in the peripartum phase [4,5], giving rise to a new clinical entity, 'gestational thrombocytopenia' [6]. In a recent longitu-dinal cohort study, we found that similar percentages of women exhibited similar and significant increases or decreases in the platelet count during the third trimester, which would explain why the mean platelet count reportedly shows no apparent change during normal pregnancy [7].…”
Section: Introductionmentioning
confidence: 76%
“…Although the pathogenesis of GT has not yet been determined, accumulating clinical experience indicates that GT is of limited obstetric or hematologic signi cance, either to the mother or to the newborn. However, the basis for this perception is derived from studies using the standard cutoff value of 150,000/ mm 3 for de ning thrombocytopeni a [4,5,8,9,12,13]. Our study using a cutoff value of 100,000/ mm 3 showed GT was virtually asymptomatic during pregnancy and delivery, and there was no severe neonatal thrombocytopenia .…”
Section: Discussionmentioning
confidence: 92%
“…After exclusion of these cases, there remains a group of women who have persistent thrombocytopenia with no identi able cause. This condition has been called epidemic [8], periparturitiona l [9], incidental [4], gestational [10], asymptomatic [11], and pregnancy-associate d thrombocytopeni a [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain why gestational thrombocytopenia is more likely to occur in twin than in singleton pregnancy. The 10 th percentile value (137×10 9 /l) of platelet count before delivery for twin pregnancies [6] corresponds to the 3 rd -4 th percentile value for singleton pregnancies [5,24,25]. Gestational thrombocytopenia of less than 100×10 9 /l was seen in 17% of twin pregnancies [26], while its rate was less than 1.0% of singleton pregnancies [27].…”
Section: Discussionmentioning
confidence: 99%